Real-time cardiac magnetic resonance tissue characterisation for fibrosis assessment in aortic stenosis. (25th November 2020) - Backhaus, S.J; Lange, T; Beuthner, B.E; Topci, R; Wang, X; Kowallick, J.T; Lotz, J; Seidler, T; Toischer, K; Zeisberg, E.M; Puls, M; Jacobshagen, C; et al.
Abstract: Background: Myocardial fibrosis is a major determinant of outcome in aortic stenosis (AS). Novel fast real-time (RT) cardiac magnetic resonance (CMR) mapping techniques allow comprehensive quantification of fibrosis but have not yet been adequately validated against standard techniques and histology. Methods: Patients with severe AS underwent CMR before (n=110) and left ventricular (LV) endomyocardial biopsy (n=46) at transcatheter aortic valve replacement (TAVR). Midventricular short axis native, post-contrast T1 and extracellular volume fraction (ECV) maps were generated using commercially available 5(3)3 MOLLI and RT single-shot inversion recovery fast low-angle shot (FLASH) with radial undersampling. ECV and LV mass were used to calculate LV matrix volumes. Variability and agreements were assessed between RT, MOLLI and histology using intraclass correlation coefficients, coefficients of variation and Bland Altman analyses. Results: RT and MOLLI derived ECV were similar for myocardium (26.2 vs. 26.5, p=0.073) and inter-ventricular septum (26.2 vs. 26.5, p=0.216). MOLLI native T1 time was in median 20 ms longer compared to RT (p<0.001). Agreement between RT and MOLLI was best for ECV (ICC >0.91), excellent for post-contrast T1 times (ICC >0.81) and good for native T1 times (ICC >0.62). Diffuse collagen volume fraction by biopsies was in median 7.8%. ECV (RT r=0.345, p=0.039; MOLLI r=0.40, p=0.010) and LV matrix volumes (RT r=0.45, p=0.005; MOLLI r=0.43, p=0.007) were the only parameters associated with histology. Conclusions: RT mapping offers precise T1 and ECV assessments with similar agreement with histology as compared to conventional MOLLI techniques. Single-shot real time techniques may be advantageous in sicker patients prone to dyspnoea or arrhythmia. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): German Research Foundation